2013
DOI: 10.1186/2193-1801-2-156
|View full text |Cite
|
Sign up to set email alerts
|

High-dose intravenous methylprednisolone for the prophylactic treatment of cluster headache

Abstract: BackgroundTriptans are effective for immediate relief of episodic cluster headache (CH) but do not reduce the frequency of attacks. Intravenous bolus injection of corticosteroids like methylprednisolone (MP) has been reported to decrease the frequency of CH attacks. We validated the prophylactic efficacy of MP pulse therapy by monitoring CH recurrence over several years following treatment of six consecutive male patients (mean age: 38.8 years, range: 26–54 years) afflicted by frequent (often daily) CH attacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…However, the exact mechanism of action of prednisolone in cluster headache is unknown. Although placebo-controlled trials are lacking, high doses of corticosteroids are highly effective in the treatment of cluster headache, as described in four open-label trials [86][87][88][89] and one case series [90]. There is no consensus on mode of administration (intravenous vs. oral), dosage or duration.…”
Section: Prednisolonementioning
confidence: 99%
“…However, the exact mechanism of action of prednisolone in cluster headache is unknown. Although placebo-controlled trials are lacking, high doses of corticosteroids are highly effective in the treatment of cluster headache, as described in four open-label trials [86][87][88][89] and one case series [90]. There is no consensus on mode of administration (intravenous vs. oral), dosage or duration.…”
Section: Prednisolonementioning
confidence: 99%
“…For oral steroids, a recent randomized controlled trial showed significant improvement with a 17 day course of prednisone (starting at 100 mg daily for five days, then titrating down by 20 mg every three days) 132. Observational studies of various oral corticosteroid pulses, as well as intravenous methylprednisolone, have also been described 133134135136137…”
Section: Treatmentmentioning
confidence: 99%
“…Corticosteroids have been delivered via occipital nerve blocks and via oral tablets; both methods of delivery have shown benefit using a variety of corticosteroids types and dosages. [134][135][136][137][138] Occipital and suboccipital nerve blocks were investigated in a meta-analysis, showing a relative risk ratio of 4.86 for freedom from pain at one month compared with control (across two randomized controlled studies and 66 participants), as well as an overall 50% freedom from pain at one month (across five randomized studies and 156 participants with cluster headache). 128 The exact components of the blocks differed widely.…”
Section: Corticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Naratriptan [ 9 , 10 ] and ramelteon [ 11 ] are also considered as alternative prophylactic options [ 9 , 10 ]. Preventative treatments are used on a scheduled basis to reduce the frequency and intensity of headaches [ 12 ]. If it is ineffective, contraindicated, or discontinued due to side effects, the choice of preventative treatment can be difficult [ 13 ].…”
Section: Introductionmentioning
confidence: 99%